Möglichkeiten empirischer Unterrichtsforschung in der Lehramtsausbildung: Das Beispiel geographischer Alltagsvorstellungen von Grundschulkindern zur Entstehung des Bodensees - Wustmann, Kathrin; Schleicher, Yvonne (Zeitschrift für Geographiedidaktik (ZGD), 2009)
By using the mental model-building strategy, authors such as Sibylle Reinfried, Stephan Schuler and Kerstin Drieling have shown in their research, that preconceptions concerning geographic issues can be identified. Therefore the question arose, whether their research-approach could be used in a modified or simplified way by students of geographic education in primary schools. Within the framework of their exams these students have to conduct a thesis, based on empirical research. After evaluating the results of a group of students it seems to be obvious, that this approach contributes substantially to the professional development of geography teachers.